2019
DOI: 10.4049/jimmunol.1800717
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Signaling Blockade during CD40-Mediated Immune Activation Favors Antitumor Factors by Reducing TGF-β, Collagen Type I, and PD-L1/PD-1

Abstract: IL-6 plays a role in cancer pathogenesis via its connection to proteins involved in the formation of desmoplastic stroma and to immunosuppression by driving differentiation of myeloid suppressor cells together with TGF-β. Inhibition of IL-6 signaling in the tumor microenvironment may, thus, limit desmoplasia and myeloid suppressor cell differentiation. CD40 signaling can further revert myeloid cell differentiation toward antitumor active phenotypes. Hence, the simultaneous use of IL-6 blockade with CD40 stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
(64 reference statements)
2
26
0
Order By: Relevance
“…This indicated that high levels of IL-6 and IL-10 in non-survivors could provide an insight for adenovirus-associated nosocomial infection. IL-6 plays a role in immunosuppression by driving differentiation of myeloid suppressor cells together with TGF-β in cancer pathogenesis [29] .…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that high levels of IL-6 and IL-10 in non-survivors could provide an insight for adenovirus-associated nosocomial infection. IL-6 plays a role in immunosuppression by driving differentiation of myeloid suppressor cells together with TGF-β in cancer pathogenesis [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, levels of serum IL-6 could be used to estimate the inflammatory status of the lung. However, immunotherapy could also increase the level of IL-6, especially in good responders, which may disturb its predictive effects [80].…”
Section: Immunologic Factorsmentioning
confidence: 99%
“…There are limited antiviral drugs available for adenovirus. Cidofovir is an antiviral drug which use has been associated with significant reductions of adenovirus load and, in some series improved survival in reports [10,23] . Until recently, Cidofovir is not available in China till 2019, and has been neither widely used in children, nor has it been used in our cases.…”
Section: Management and Outcomesmentioning
confidence: 99%